Dance in virtual reality for Alzheimer's rehabilitation : DAVIMU (2016)
The Dance in Virtual Reality for Alzheimer Rehabilitation project aims to propose a solution against dependency, isolation and balance issues, which are typical of aged people who suffer from Alzheimer's disease. For this purpose, the project takes as a premise the use of the perception effect in Alzheimer?s patients, based on their socio-cultural environment as music, with the help of technological tools such as virtual reality. This will result in the creation of DAVIMU which is a tool that is adapted to the user's motor, cognitive and balance capabilities while dancing, in order to enhance these skills